Multivessel primary PCI in patient with peripheral arterial disease - K.C., Bishal; Adhikari, Chandra Mani; Rauniyar, Binay Kumar; Limbu, Deepak; Malla, Rabi (Nepalese Heart Journal, 2017)
Thrombosis of multiple coronary arteries is extremely rare finding in the setting of acute myocardial infarction. This often leads to cardiogenic shock and sudden cardiac death. We report a case of 61 years old gentleman who presented with complaints of sudden onset of chest pain of 4hours duration and dizziness with near syncope 2 hours prior to presentation and ST segment elevation in anterior and inferior leads with complete heart block. Coronary angiogram revealed total occlusion of left anterior descending (LAD) and right coronary arteries (RCA). After the PCI to RCA follwed by LAD, patient went into Pulse less electrical activity. Cardiopulmonary resuscitation, immediate percutaneous coronary intervention of the LAD and RCA, temporary pacing, immediate intubation and mechanical ventilation was carried out. The patient was eventually discharged with a New York Heart Association functional class II heart failure.Nepalese Heart Journal 2017; 14(1): 35-38